Wokół struktury mitu Michała Drzymały - Leśniewska, Inga (Acta Universitatis Lodziensis. Folia Historica, 2005)
The myth of Michał Drzymała is one of those, which were created on the turn of 19th century, to reinvigorate Poles during the time when Poland was portioned. Prussian policy concentrated on divest of Polish national character was such a threat, that it had to be answered. Ethos of peasant hero, who defended his land, understood as homeland, regardless of consequences seemed to be the best way to strength national identity among peasants. However, the chance to adopt this myth in common consciousness was possible, when he was described as seemingly ordinary, nevertheless clever man. In order to obtain such an ideal and suggestive personage, some facts, that did not match the picture of Michał Drzymała - Polish hero, had to be hidden from the public. Basic components of any myth are a symbol and an essence. In that case the symbol is the wagon, but it can be understood only with the essence, created by the Michal Drzymala’s story. Furthermore it does not mean that there is a myth. Without publicity and dynamic propaganda campaign First in the press, than in literature, the myth would not exists. In spite of this it did not become timeless archetype, because it was short of some features to build widespread status in the common sense.